"Either Everyone Was Guilty or Everyone Was Innocent"1: The Italian Power Elite, Neopatrimonialism, and the Importance of Social Relations. (April 2018) - Doidge, Mark
Rarely does the Byzantine world of football administration get exposed as clearly as during the 2006 calciopoli scandal. This scandal laid bare the interpersonal relationships of football administrators at the top three Italian men's football clubs: Juventus, Inter, and AC Milan. This article draws on the media leaks that revealed the inner workings of those working within football to argue that the football clubs are pyramids of power for club presidents that allows them to operate within the Italian power elite. This is done through interpersonal clientelistic networks that operate within a neopatrimonial system. Theoretically, this article draws on four main concepts: C. Wright Mills's concept of the Power Elite, Lomnitz's model of "Pyramids of Power, " Eisenstadt's notion of neopatrimonialism, and Mauss's utilization of the gift. Power is exercised through quid pro quo relationships, with certain key individuals operating as brokers to the flow of favors throughout the network.